A phase 1 study of the safety, pharmacokinetics and pharmacodynamics of escalating doses followed by dose expansion of the selective inhibitor of nuclear export (SINE) selinexor in Asian patients with advanced or metastatic malignancies - Ho, Jingshan (SAGE PUBLICATIONS LTD, 2022)
10.1177/17588359221087555